1994
DOI: 10.1111/j.1745-4573.1994.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF PROCESSING VARIABLES ON MICROBIAL QUALITY AND SHELF‐LIFE OF BLUE CRAB (CALLINECTES SAPIDUS) MEAT

Abstract: The ejfects of cooking time, cooking method, season, and storage condition on the microbiological quality, sensory characteristics, and shelf-life of crabmeat were determined under commercial processing conditions. Microbial flora content of the meat was inversely proportional (p < 0.05) to the cooking time in both total aerobic and anaerobic plate counts afer 6 and 9 days at 2.2C during summer. Boiled cooked crabmeat showed higher microbial count (1-2 log cycle) and shorter shelf-lives than I0 and 12 min reto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The study shows a significant reduction in bacterial load, as a result of cooking and freezing. The results obtained are similar to the findings of Hong and Flick (1994) in crabmeat, wherein the bacterial content was determined to be inversely proportional to cooking time. A similar study on raw shrimp showed total aerobic plate count (APC) below 10 5 , while cooked shrimp had less than 10 4 (Mohamed Hatha et al .…”
Section: Discussionsupporting
confidence: 88%
“…The study shows a significant reduction in bacterial load, as a result of cooking and freezing. The results obtained are similar to the findings of Hong and Flick (1994) in crabmeat, wherein the bacterial content was determined to be inversely proportional to cooking time. A similar study on raw shrimp showed total aerobic plate count (APC) below 10 5 , while cooked shrimp had less than 10 4 (Mohamed Hatha et al .…”
Section: Discussionsupporting
confidence: 88%
“…The alternative, manual extraction of meat, is uneconomical and also introduces the risk of high levels of contamination. 4 Meat extraction from a seafood, using a chemical solution having a known speci®c gravity, has been investigated by Tretsven, 5 Learson et al 6 and Chakrabarti. 7±9 Dense media separation has been described by Bronkala 10 as a means of separating solids of differing speci®c gravities by immersing them in a liquid of speci®c gravity intermediary between those of the solids to be separated.…”
Section: Introductionmentioning
confidence: 99%